Comparison and Analysis of Thermal Degradation Process of Aramid Fibers (Kevlar 49 and Nomex) (Journal of Fiber Bioengineering and Informatics, 2018)
High performance fibers such as polymer material, have extensive applications in aerospace and high temperature environment. When these fibers were used in such high temperature, could be subjected to degradation. To understand and evaluate the thermal degradation process of materials under thermal environment, effective characterization and research methods must be adopted. In this paper, the thermal degradation processes of aramid fibers were analysed by TGA-DTA/FT-IR. The experimental results show that aramid fibers (Kevlar 49, Nomex) have similar thermal stability, but their thermal degradation process and temperatures are different. Kevlar 49 fiber shows higher degradation temperature as a copolymer of para-aramid, and its initial degradation temperature is 548.1°C in air. It can also be found that the Nomex fiber has a lower thermal degradation temperature and its initial degradation temperature is 423.7°C in air. Ascending the temperature to 800°C, the two kinds of fibers loose all mass in air. We can get the wave number, absorbance time and three-dimensional images during the heating process by TGA-DTA/FT-IR tests. According to TG curves, the infrared spectra of decomposition products can be obtained and analyzed. The thermal decomposition process can be comprehensively discussed by the infrared spectra of decomposition products.